Lithium secondary battery and method of manufacturing same

Through the method of lamination molding and external pressure injection of electrolytes during the packaging process of lithium sulfur batteries, the problems of uniform infiltration and volume expansion of electrolytes in high-density electrodes are solved, and the performance and life of the battery are improved.

JP7659072B2Active Publication Date: 2025-04-08LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023541994
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-12
Filing Date
2022-10-12
Publication Date
2025-04-08
Estimated Expiration
2042-10-12

AI Technical Summary

Technical Problem

In the existing lithium-sulfur secondary batteries, in high-density electrode materials, the electrolyte is difficult to uniformly infiltrate, and the volume expansion problem is serious, which affects the electrochemical performance and life of the battery.

Method used

During the packaging process of lithium sulfur batteries, the positive electrode, separator and negative electrode are first laminated and then injected with electrolyte under external pressure to ensure that the electrolyte is evenly distributed on the high-density electrode.

Benefits of technology

The low volume expansion and high electrolyte uniformity of lithium-sulfur batteries are achieved, and the performance and life of the batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659072000002
    Figure 0007659072000002
  • Figure 0007659072000003
    Figure 0007659072000003
  • Figure 0007659072000004
    Figure 0007659072000004
Patent Text Reader

Abstract

The lithium secondary battery according to the present invention is manufactured by injecting an electrolyte in a pressurized environment, whereby a small amount of electrolyte can be uniformly supported on a low-porosity, high-density electrode, improving the performance and life characteristics of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to Korean Patent Application No. 10-2021-0134880, filed on October 12, 2021.

[0002] The present invention relates to a lithium secondary battery, and more particularly to a lithium secondary battery with minimized volume expansion, a manufacturing system for a lithium secondary battery with minimized volume expansion, and a manufacturing method for a lithium secondary battery with minimized volume expansion. [Background technology]

[0003] The reference or discussion in this specification to certain documents, acts or knowledge is not an admission that such documents, acts, knowledge, or any combination of two or more of them, were published, publicly available, known to the public, part of common general knowledge, or constitute prior art under any applicable provision of law or were known to be relevant to any attempt to solve any problem related to this specification, as of the priority date.

[0004] In recent years, the demand for portable electronic products such as laptop computers, video cameras, and mobile phones has increased significantly. In addition, the development of electric vehicles, energy storage batteries, robots, satellites, etc. has increased dramatically. As a result, research and development of high-performance secondary batteries has been actively carried out.

[0005] Unlike common primary batteries, secondary batteries can be repeatedly charged and discharged. Therefore, for example, a low-capacity secondary battery with one battery cell packaged in a pack can be used in portable electronic devices such as mobile phones, laptops, and camcorders. Or, a high-capacity battery with a battery pack unit in which dozens of battery cells are connected to each other can be used as a power source for driving the electric motor of an electric vehicle or hybrid electric vehicle.

[0006] Currently, nickel-cadmium batteries, nickel-metal hydride batteries, nickel-zinc batteries, lithium-ion secondary batteries, etc. are commercially available secondary batteries. Among these batteries, lithium secondary batteries have attracted attention due to their relatively low self-discharge rate, low battery memory effect, and high energy density characteristics compared to nickel-based secondary batteries. In particular, among lithium-ion secondary batteries, lithium-sulfur (Li-S) secondary batteries are currently in the spotlight as next-generation batteries that can exhibit high energy density. However, the materials currently used to manufacture Li-S secondary batteries have a relatively low density. For example, the density of the positive electrode containing sulfur in Li-S batteries is low, about 0.3 to 0.6 g / cc. Due to the low density characteristics of the positive electrode, it is difficult to improve the performance of Li-S secondary batteries.

[0007] Therefore, research and development of high-density electrodes for Li-S batteries is being continuously conducted to improve the efficiency and performance of Li-S batteries. However, when the density of the electrode is increased, the porosity decreases, making it difficult to uniformly impregnate the electrolyte. In addition, volume expansion may occur during battery operation, which may result in a decrease in the electrochemical performance of the battery and / or a decrease in battery life. For this reason, there is a strong demand for the development of Li-S batteries using high-density electrodes in which the electrolyte is uniformly or evenly impregnated while swelling is reduced or minimized.

[0008] On the other hand, the description of the background art provided herein is intended to generally present the context of the present disclosure, and unless otherwise indicated herein, the materials described in this Background Art are not prior art to the claims of the present invention and are not admitted as prior art or suggested prior art merely by virtue of their inclusion in the Background Art section. Summary of the Invention [Problem to be solved by the invention]

[0009] The present invention is to solve the above-mentioned technical problems. As a result of extensive research into solving the above-mentioned problems, the present inventors have confirmed that in a manufacturing process of a pouch cell type lithium secondary battery, when a laminate in which a positive electrode, a separator (separation membrane) and a negative electrode are sequentially laminated is inserted into a pouch, the pouch is pressurized from the outside to fix the thickness, and an electrolyte is then injected into the pouch, a small amount of electrolyte can be uniformly supported on the high density electrode, thereby improving the life characteristics of the battery.

[0010] SUMMARY OF THE PRESENT EMBODIMENT An object of the present invention is to provide a pouch cell type lithium secondary battery in which an electrolyte is uniformly distributed, and a method for manufacturing the same. [Means for solving the problem]

[0011] It has been discovered that the disclosed subject matter can address the aforementioned shortcomings and achieve certain advantages, for example, the batteries, methods, and systems of the present disclosure provide a novel approach to minimizing the swelling of lithium secondary batteries.

[0012] It is to be understood that the various individual aspects and features of the invention described herein may be combined in any number with any one or more of the individual aspects or features to form embodiments of the invention that are specifically considered, and such combinations are also within the scope of the present disclosure.

[0013] The present invention relates to a lithium-sulfur battery having a sulfur-based compound as a positive electrode active material.

[0014] In a first aspect of the present invention, the battery includes an electrode assembly having a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, a pouch accommodating the electrode assembly, and an electrolyte, and the lithium-sulfur battery has an expansion coefficient SF according to the following formula 1 that is greater than or equal to 0 and less than 10: [Formula 1] SF = (T2-T1) / (T1) x 100 where T1 is the first thickness of the lithium-sulfur battery and T2 is the second thickness of the lithium-sulfur battery.

[0015] A second aspect of the present invention is the lithium-sulfur battery according to the first aspect, wherein the first thickness is a thickness of the lithium-sulfur battery before injecting an electrolyte into the pouch, and the second thickness is a thickness of the lithium-sulfur battery after injecting an electrolyte into the pouch.

[0016] A third aspect of the present invention is a lithium-sulfur battery according to the first or second aspect, wherein the first thickness and the second thickness are both measured after an electrolyte is injected, and the first thickness and the second thickness are each measured at an arbitrary location of the battery, and the locations at which the first thickness and the second thickness are measured are different from each other.

[0017] A fourth aspect of the present invention is the lithium-sulfur battery according to any one of the first to third aspects, wherein the positive electrode contains a sulfur-carbon composite having a carbon material and sulfur as a positive electrode active material.

[0018] A fifth aspect of the present invention is the lithium-sulfur battery according to the fourth aspect, wherein a weight of sulfur is 70% or more with respect to a total weight of the sulfur-carbon composite.

[0019] A sixth aspect of the present invention is the lithium-sulfur battery according to any one of the first to fifth aspects, wherein the positive electrode has a positive electrode active material layer having a density of 0.5 g / cc to 4.5 g / cc.

[0020] A seventh aspect of the present invention is the lithium-sulfur battery according to any one of the first to sixth aspects, wherein the negative electrode contains lithium metal as a negative electrode active material.

[0021] An eighth aspect of the present invention is the lithium-sulfur battery according to any one of the first to seventh aspects, wherein the ratio of the weight of the electrolyte to the weight of the sulfur, E / S, is 2.7 or less.

[0022] A ninth aspect of the present invention is the lithium-sulfur battery according to any one of the first to eighth aspects, wherein the positive electrode active material layer of the positive electrode has a porosity of 35 vol % to 75 vol %.

[0023] A tenth aspect of the present invention is a lithium-sulfur battery according to any one of the first to ninth aspects, wherein the capacity of the battery is 950 mAh / g s ~1300mAh / g s It is what it is.

[0024] An eleventh aspect of the present invention is an electrochemical device including the lithium-sulfur battery according to any one of the first to tenth aspects as a power source, the electrochemical device including an electric vehicle.

[0025] A twelfth aspect of the present invention relates to a method for manufacturing a lithium-sulfur battery, the method including the steps of: laminating a positive electrode, a separator, and a negative electrode to form an electrode assembly; housing the electrode assembly in a pouch; applying a predetermined pressure to the pouch housing the electrode assembly; injecting a predetermined amount of electrolyte into the pouch while maintaining the predetermined pressure; and sealing the pouch, wherein the lithium-sulfur battery has an expansion coefficient SF of 0 or more and less than 10 according to the following formula 1: [Formula 1] SF = (T2-T1) / (T1) x 100 where T1 is the first thickness of the lithium-sulfur battery and T2 is the second thickness of the lithium-sulfur battery.

[0026] A thirteenth aspect of the present invention is the method for manufacturing a lithium-sulfur battery according to the twelfth aspect, further comprising the step of measuring an expansion coefficient before sealing the pouch.

[0027] A fourteenth aspect of the present invention is the method for manufacturing a lithium-sulfur battery according to the thirteenth aspect, wherein the step of measuring the expansion coefficient includes the steps of measuring a first thickness of the lithium-sulfur battery before injecting an electrolyte into the pouch, and measuring a second thickness of the lithium-sulfur battery after injecting an electrolyte into the pouch.

[0028] A fifteenth aspect of the present invention relates to a method for manufacturing a lithium-sulfur battery according to any one of the twelfth to fourteenth aspects, further comprising a step of measuring an expansion coefficient after sealing the pouch.

[0029] A sixteenth aspect of the present invention is the method for manufacturing a lithium-sulfur battery according to the fifteenth aspect, wherein the step of measuring the expansion coefficient comprises the steps of measuring a first thickness of the battery in a first region of the lithium-sulfur battery and measuring a second thickness of the battery in a second region of the lithium-sulfur battery.

[0030] A seventeenth aspect of the present invention is the method for producing a lithium-sulfur battery according to any one of the twelfth to sixteenth aspects, wherein the amount of pressure is 100 atm or less.

[0031] An eighteenth aspect of the present invention relates to a system for manufacturing a lithium-sulfur battery, the system including: a control device; a jig connected to the control device, the jig having a first plate and a second plate, the jig applying pressure between the first plate and the second plate, the amount of the pressure being based on an expansion coefficient of the lithium-sulfur battery; and an electrolyte injection device connected to the control device, the jig injecting an electrolyte into a pouch of the lithium-sulfur battery, the expansion coefficient SF being expressed by the following formula 1: [Formula 1] SF = (T2-T1) / (T1) x 100 where T1 is the first thickness of the lithium-sulfur battery and T2 is the second thickness of the lithium-sulfur battery.

[0032] A 19th aspect of the present invention is to manufacture a lithium-sulfur battery in the system for manufacturing a lithium-sulfur battery according to the 18th aspect, further comprising a controller for adjusting the amount of pressure applied to the lithium-sulfur battery based on the expansion coefficient. Effect of the Invention

[0033] The method for manufacturing a lithium secondary battery according to the present invention is characterized in that an electrolyte injection step is performed in which an electrolyte is injected into the battery under a pressurized environment. This minimizes the volume expansion of the battery due to the electrolyte, and a small amount of electrolyte can be uniformly supported on a high-density electrode with low porosity, thereby improving the performance and life characteristics of the battery. In addition, the method can provide a battery having a uniform thickness and a small change in volume before and after electrolyte injection. In particular, in the case of a lithium-sulfur battery, it is preferable to reduce the porosity of the positive electrode active material layer in order to increase the energy density, and the electrolyte can be uniformly supported on such a low-porosity positive electrode and an electrode assembly including the same.

[0034] In the case where the battery is a pouch type, the volume expansion of the battery can be controlled by applying pressure, so that the manufacturing method of the present invention is particularly effective.

[0035] The following drawings attached to this specification are illustrative of a specific embodiment of the present invention, and serve to further understand the technical concept of the present invention together with the detailed description of the invention. Therefore, the present invention should not be interpreted as being limited to only the matters described in such drawings. Meanwhile, the shape, size, scale, ratio, etc. of elements in the drawings included in this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0036] [Figure 1] FIG. 1 is a schematic diagram illustrating an exemplary lithium secondary battery according to one embodiment of the present invention. [Figure 2a]FIG. 2 is a schematic diagram illustrating an exemplary lithium secondary battery prior to injection of an electrolyte into the battery in accordance with one aspect of the present invention. [Figure 2b] FIG. 2 is a schematic diagram illustrating an exemplary electrode assembly of a lithium secondary battery according to one embodiment of the present invention. [Diagram 3] FIG. 1 is a schematic diagram of an exemplary system for manufacturing a lithium secondary battery according to one embodiment of the present invention. [Figure 4a] FIG. 1 is a schematic diagram illustrating an exemplary lithium secondary battery for measuring swelling ratio according to one embodiment of the present invention. [Figure 4b] FIG. 1 is a schematic diagram illustrating an exemplary lithium secondary battery for measuring a swelling factor according to one embodiment of the present invention. [Diagram 5] 4 is a flow chart illustrating an exemplary method for manufacturing a lithium secondary battery for the battery manufacturing system of FIG. 3 according to one embodiment of the present invention. [Figure 6] 1 is a graph comparing the initial discharge capacity of a secondary battery Li-S produced according to one embodiment of the present invention with other secondary batteries Li-S. [Figure 7] 1 is a graph comparing the discharge cycle characteristics of a secondary battery Li-S produced according to an embodiment of the present invention and a secondary battery Li-S of a comparative example. [Figure 8] FIG. 1 is a schematic diagram showing a shape in which the thickness of a battery is made uneven due to volume expansion at the position of a filling port during electrolyte injection. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] Further aspects, features, and advantages of the present disclosure will become apparent from the following detailed description.

[0038] As used herein, the singular forms of terms (such as "a," "an," and "the") include the plural forms unless the context clearly indicates otherwise. Additionally, the use of "or" includes "and / or" unless the context clearly indicates otherwise.

[0039] As used herein, "about" is a term of approximation and includes minor variations in the literally referred quantity as would be understood by one of ordinary skill in the art. Such variations include, for example, the standard deviations associated with techniques commonly used to measure the amounts of components or components of an alloy or composite material, or other properties and characteristics. All values ​​characterized by the above modifier "about" also include the exact numerical values ​​disclosed herein. Additionally, all ranges include the upper and lower limits.

[0040] Any composition described herein is intended to encompass compositions that consist of or consist essentially of the various components identified herein, as well as compositions that include the various components identified herein, unless otherwise specified.

[0041] As used herein, the recitation of a numerical range for a variable is intended to convey that the variable can be equal to any value within that range, as well as any and all subranges encompassed by the broader range. Thus, the variable can be equal to every integer value within the numerical range, including the end points of the range. For example, a variable described as having values ​​from 0 to 10 can be equal to 0, 4, 2 to 6, 2.75, 3.19 to 4.47, etc.

[0042] In this specification and claims, the singular forms include plural referents unless the phrase specifically states otherwise. As used herein, unless otherwise indicated, the word "or" is used in the inclusive sense of "and / or" and not in the exclusive sense of "either one / or."

[0043] Unless otherwise specified, each individual feature or example herein can be combined, without limitation, with any other individual feature or embodiment described herein, and such combinations are specifically contemplated as being within the scope of the present disclosure, whether or not they are expressly described as combinations herein.

[0044] Unless otherwise defined, technical and scientific terms used herein have the meaning commonly understood by one of ordinary skill in the art to which this invention belongs. Reference is made herein to various methodologies and materials known to those skilled in the art.

[0045] Even when used in conjunction with the detailed description of specific examples of the present disclosure, the terms may be interpreted in the broadest and most reasonable manner. Indeed, certain terms may be emphasized below. However, any terms intended to be interpreted in a restrictive manner are expressly and specifically defined in this detailed description section. Of the contents described in the specification, both the general description and the detailed description are merely exemplary and explanatory, and do not limit the features described in the claims.

[0046] As used herein, the terms "for example" and "exemplary" are used in the sense of merely "example," not "preferred" or "ideal." The term "or" is inclusive and means some or all of the listed items. The terms "comprise(s), comprising, include(s), including" and other variations thereof mean that the process, method, or product that includes components is not necessarily limited to only those elements, and may include other elements not expressly listed or inherent to such process, method, article, or apparatus.

[0047] One aspect of the present invention relates to a lithium secondary battery that can be manufactured by inserting an electrode assembly into a housing of the lithium secondary battery. The electrode assembly may include a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode. In one embodiment of the present invention, the electrode assembly may include a plurality of positive electrodes and a plurality of negative electrodes that are stacked in a repeated manner. For example, a positive electrode may be provided as a first layer of the electrode assembly. Then, a separator may be stacked on the top of the positive electrode, and a negative electrode may be stacked on the top of the separator. Furthermore, another separator may be provided on the top of the negative electrode, or another positive electrode may be stacked. Also, the electrode assembly may be a stack type or a stack / folding type in which the electrodes and a separator are stacked in sequence, or may be a jelly roll type. The electrode assembly thus prepared may then be inserted into a battery housing. For example, the battery housing may have the form of a pouch including a metal can or a polymer film, but is not limited thereto.

[0048] For example, a pouch-type battery (or pouch-type battery cell) may be formed by inserting an electrode assembly (e.g., a stacked electrode assembly or a jelly-roll electrode assembly) into a pouch. An electrolyte may then be injected into the pouch and sealed to assemble the pouch-type battery cell. The electrolyte injected into the pouch may flow into and fill pores present in the electrode assembly and simultaneously fill the pores in the housing other than the volume (apparent volume) occupied by the electrode assembly. The pores may include pores formed in one or more of the positive electrode, negative electrode, and separator, and may be the positive electrode. In this way, the amount of electrolyte to be injected into the pouch may be predetermined before the electrolyte is injected into the pouch, thereby ensuring uniform impregnation and preventing overflow of excess electrolyte. Therefore, a change in the thickness of the pouch cell (or battery cell) detected after injecting an electrolyte into the pouch cell means that the electrolyte is unevenly distributed or impregnated in the electrode assembly, particularly the positive electrode.

[0049] As previously mentioned, in Li-S batteries, non-uniform electrolyte impregnation can occur due to low porosity of one or more electrodes (e.g., the high density positive electrode). Thus, if the high density positive electrode of a Li-S battery is not uniformly impregnated with electrolyte, excess electrolyte can expand and cause battery defects, reducing performance and battery life.

[0050] According to one aspect of the present invention, there is provided a lithium ion secondary battery including a high density electrode and minimizing swelling. In one aspect, the lithium secondary battery according to the present invention has a swelling factor (SF) according to the following formula 1 of 0 or more and less than 10, 0 or more and 7 or less, or 0 or more and 5 or less.

[0051] [Formula 1] SF=(T2-T1) / (T1)×100, In the above formula 1, T1 means the first thickness and T2 means the second thickness.

[0052] In one embodiment of the present invention, the first thickness is the thickness at any point of the battery before the electrolyte is injected, and the second thickness is the thickness of the battery after the electrolyte is injected (embodiment A). In this case, it is preferable that the first thickness and the second thickness are measured at the same point before and after the electrolyte is injected. Meanwhile, in one embodiment of the present invention, the SF may be a value obtained by averaging values ​​measured at two or more points. In one embodiment of the present invention, the SF may be measured at two or more or three or more points. Meanwhile, the second thickness may be measured before or after the battery is sealed.

[0053] In one embodiment of the present invention, in the embodiment A, the battery is injected with an electrolyte solution while applying an external pressure to the battery, and in this case, the T2 may be measured while the pressure is maintained after the electrolyte solution is injected, or may be measured while the pressure is released. Since the T1 is a value measured before the electrolyte solution is injected, the thickness may be substantially the same whether the pressure is applied or not.

[0054] Additionally or alternatively, the first thickness may be a thickness measured at one arbitrary point of the battery, and the second thickness may be a thickness measured at another arbitrary point (embodiment B). Hereinafter, when it is necessary to distinguish from SF of embodiment A, it is indicated as SF'. In the SF', the first thickness and the second thickness may be measured after the electrolyte is injected. Also, the first thickness and the second thickness may be measured before or after sealing the pouch after the electrolyte is injected. Also, in one embodiment of the present invention, the first thickness and the second thickness may be a combination of two values ​​selected from a plurality of values ​​measured at two or more arbitrary points, which have the largest SF. Whether the thickness of the battery is uniform after the electrolyte is injected can be confirmed by the SF'. That is, according to embodiment B, the deviation of the thickness of the battery after the electrolyte is injected can be confirmed, and therefore, whether the electrolyte is flowing uniformly into the electrode assembly can be confirmed. Meanwhile, in embodiment B, the electrolyte is injected into the battery while applying an external pressure to the battery, and both the first thickness and the second thickness may be measured while applying the pressure or while releasing the pressure.

[0055] In the lithium secondary battery according to the present invention, the SF value according to embodiment A may be 0 or more and less than 10, 0 or more and 7 or less, or 0 or more and 5 or less.

[0056] Additionally or alternatively, the lithium secondary battery according to the present invention may have an SF value (SF') according to embodiment B of 0 or more and 7 or less, 0 or more and 5 or less, 0 or more and 3 or less, or 0 or more and 1 or less.

[0057] In one embodiment of the present invention, the battery may satisfy at least embodiment A, or may satisfy both embodiment A and embodiment B.

[0058] In the battery according to the present invention, the electrolyte is injected under pressure, so that the volume expansion of the battery is suppressed. Therefore, when the SF value according to embodiment A is a value less than 10, the SF value according to embodiment B can be substantially equal to or less than 7.

[0059] The SF values ​​described below will be mainly explained with reference to embodiment A. However, the explanation of embodiment B is not excluded, and it goes without saying that the explanation can also be applied to embodiment B.

[0060] In the lithium ion secondary battery, when the value of SF according to the formula 1 is 0 or more and less than 10 (0≦SF<10), 0 or more and 7 or less (0≦SF≦7), or 0 or more and 5 or less (0≦SF≦5), it indicates that the lithium secondary battery hardly swells or does not swell at all. Preferably, the SF is 0 or more and 5 or less. For the SF in embodiment B, the above-mentioned range can be referred to.

[0061] Meanwhile, in the present invention, the thickness refers to the height of the battery in the direction in which battery components such as electrodes and separators are stacked based on the electrode assembly.

[0062] According to a specific embodiment of the present invention, a lithium ion secondary battery that minimizes or does not cause swelling at all, for example, a lithium secondary battery that satisfies 0≦SF<10, or 0≦SF≦7, or 0≦SF≦5, can be manufactured.

[0063] Such a lithium secondary battery may be manufactured by inserting an electrode assembly (e.g., a stacked electrode assembly, a jelly roll type electrode assembly, etc.) into a battery housing. The housing may then be placed in a jig that applies a predetermined pressure to one or more surfaces of the battery housing. For example, the housing may be a pouch used in a pouch type battery, but is not limited thereto. In one embodiment of the present invention, the effect of the present invention can be more effectively achieved when the housing is a pouch compared to when the housing is a metal can. In the case of a metal can, the volume expansion can be suppressed due to the rigidity of the metal. However, a pouch type exterior material has a lower rigidity than a metal can and is easily deformed by an external force. Therefore, when a pouch type exterior material is used to manufacture a battery according to the present invention, the effect can be maximized. However, even when a metal can is used as a housing material, it goes without saying that the improved effect of the manufacturing method of the battery according to the present invention can be achieved depending on the metal material used and its inherent properties.

[0064] Then, the electrolyte is injected into the pouch, and the electrolyte can be uniform or uniformly impregnated in the electrode assembly, particularly in the positive electrode, by a predetermined pressure applied by the jig. For example, the Li-S battery manufactured according to the present invention may include a high density positive electrode and an electrolyte uniformly impregnated in the high density positive electrode. Such a Li-S battery can satisfy 0≦SF<10, preferably 0≦SF≦5, thereby minimizing or eliminating volume expansion. In addition, the high density positive electrode of the Li-S battery according to the present invention has a structure that reduces the porosity and improves the energy density. Therefore, when the range of 0≦SF<10 is satisfied after the electrolyte is injected, the amount of electrolyte required to drive the Li-S battery can be substantially reduced, improving the battery performance and the battery life.

[0065] According to one embodiment of the present invention, a change in thickness of a lithium secondary battery can be detected or determined by identifying one or more arbitrary positions of the battery housing before injecting the electrolyte and measuring the thickness at each position before and after the electrolyte is injected. When there is one measurement position, the value may be taken as the thickness value, and when there are two or more measurement positions, the average of the individual values ​​may be taken as the thickness value. Alternatively, as described above, when two or more measurement positions are identified, the average of the SF values ​​calculated at each position may be taken as the overall SF value.

[0066] Meanwhile, alternatively or additionally, after the battery is fully assembled (e.g., after the electrolyte injection is completed or after the battery cell is sealed in a pouch after the electrolyte injection is completed), a change in the thickness of the battery may be detected or determined by measuring the unevenness of the surface of the lithium secondary battery (the difference between the first thickness and the second thickness may be the SF value).

[0067] The present invention will now be described in more detail with reference to the accompanying drawings. The description of the invention according to the drawings has been described with respect to a particular aspect of the invention, and the present invention is shown in the drawings, but is not limited to the specific aspect based on the drawings. Here, an embodiment or aspect described as "exemplary" should not be construed as being preferable or advantageous over other embodiments or aspects, for example. Rather, it is intended to reflect or show that the embodiment is an "exemplary" embodiment. The subject matter of the present invention can be realized in various different forms, and therefore, the scope of the invention should not be construed as being limited by any exemplary embodiment described herein. The exemplary embodiments are provided for illustrative purposes only. Therefore, within the scope that can be reasonably interpreted based on this specification, the scope of the present invention, particularly the claims, includes a broader scope than those exemplified. Above all, for example, the technical idea or subject matter of the present invention can be realized as a method, device, component, or system. Thus, the embodiment can take the form of, for example, hardware, software, firmware, or any combination thereof (excluding software itself). For this reason, the following detailed description is not intended to be construed in a limiting sense.

[0068] Throughout this specification and the claims, the terms used may have subtle meanings suggested or implied in the context beyond the meaning explicitly stated. Similarly, the phrase "in one embodiment" used herein does not necessarily refer to the same embodiment, and the phrase "in another embodiment" used herein does not necessarily refer to other embodiments. For example, the claimed subject matter is intended to include any combination of the example embodiments, in whole or in part.

[0069] The present invention will now be described in further detail with reference to the accompanying drawings.

[0070] FIG. 1 is a schematic diagram showing an exemplary lithium secondary battery 100 according to an embodiment of the present invention. The lithium secondary battery 100 may include an electrode assembly (not shown), a housing 102, a first electrode tab, and a second electrode tab 106. For example, the housing 102 may be a pouch as shown in FIG. 1. However, the housing 102 may be, but is not limited to, a rectangular housing, a cylindrical housing, and the like. The first electrode tab 104 may be a positive electrode tab, and the second electrode tab 106 may be a negative electrode tab, or vice versa. The first electrode tab 104 and the second electrode tab 106 may be electrically coupled to an electrode assembly (shown in detail in FIG. 2B below) of the lithium secondary battery 100. In one embodiment, the first electrode tab 104 may be electrically connected to one or more positive electrodes of the electrode assembly. Also, the second electrode tab 104 may be electrically connected to one or more negative electrodes of the electrode assembly. In FIG. 2, the first electrode tab 104 and the second electrode tab 106 are shown to be disposed on both sides (opposite each other) of the lithium secondary battery 100, however, the first electrode tab 104 and the second electrode tab 106 are not limited to this and may be disposed on any side or position of the lithium secondary battery 100, either individually or together.

[0071] FIG. 2a is a schematic diagram showing a lithium secondary battery 200 according to one side of the present invention before injecting an electrolyte. The battery 200 may include a housing (e.g., a pouch), an electrode assembly 210, and an empty volume (or empty space, e.g., a dead space) 204. The housing 102 may include an opening 202, and in the manufacturing process of the battery 100 of the present invention, the electrolyte may be injected into the housing through the opening 202, and the electrolyte may flow into the inside of the electrode assembly 210 (e.g., the pores of the electrode) to impregnate the electrode assembly with the electrolyte. Any remaining electrolyte may be filled or dispersed in the empty space 204. The empty space 204 is a space generated when a substantially sheet-like pouch film is deformed (e.g., folded or bent) to accommodate an electrode assembly of a specific shape. Therefore, it is preferable that the internal space of the housing conforms (fits) to the shape of the electrode assembly so that such an empty space does not occur. However, the volume of the inner space of the housing actually exceeds the volume (apparent volume) of the electrode assembly to be accommodated, and therefore an empty space is generated. When manufacturing a battery, it is preferable to design the empty space of the housing to be minimized. In one embodiment of the present invention, excess electrolyte remaining without being impregnated in the electrode assembly 210 may be stored in the empty space 204. In this way, when manufacturing a battery, a certain amount of empty space 204 is actually generated, and when injecting the electrolyte, the injection amount of the electrolyte is determined taking into account the volume of the empty space. Meanwhile, when the amount of electrolyte injected into the housing 102 is approximately equivalent to the volume of the pores of the electrode assembly 210 and the volume of the empty space, and the electrolyte is uniformly impregnated into the electrode assembly, the thickness of the battery 200 after the electrolyte is injected may be approximately the same as the thickness of the battery before the electrolyte is injected.

[0072] 2b is a schematic diagram of an exemplary electrode assembly 210 of a battery 200 (or a battery) according to an embodiment of the present invention. The electrode assembly 210 may include one or more positive electrodes 212, one or more separators 214, and one or more negative electrodes 216. For example, the electrode assembly 210 may be formed by repeatedly stacking positive electrodes 212, separators 214, and negative electrodes 216, and stacking a final layer 218 (either a positive electrode layer or a negative electrode layer, depending on the stacking order and stacking direction). The number of negative electrodes, positive electrodes, and separators included in the electrode assembly may be based on the desired capacity and / or function of the electrode assembly 210 for the battery 100 or 200, for example.

[0073] According to one embodiment of the present invention, the positive electrode 212 may include at least a positive electrode current collector and a positive electrode active material layer (not shown) disposed on at least one surface or both surfaces of the positive electrode current collector.

[0074] The positive electrode current collector may include, but is not limited to, a conductive (electrically conductive) material such as aluminum foam, nickel foam, etc. The positive electrode active material layer may include, for example, a positive electrode active material, a binder, and a conductive material (conductive material).

[0075] The content of the entire positive electrode active material in the positive electrode active material layer may be about 70% to 95% of the total weight of the positive electrode active material layer. If the ratio of the positive electrode active material contained in the positive electrode active material layer is less than the above-mentioned 70% to 95% (e.g., less than 60%), the capacity of the battery 100 may decrease. If the ratio of the positive electrode active material exceeds the above range (e.g., exceeds 95%), an overvoltage of the battery 100 may occur.

[0076] In one aspect of the present invention, the positive electrode active material may contain, for example, a sulfur-based positive electrode active material, and preferably, the positive electrode active material contains 70 wt% or more, 80 wt% or more, 90 wt% or more, or 99 wt% or more of the sulfur-based positive electrode active material. In a specific embodiment of the present invention, the positive electrode active material may contain 90 wt% or more of the sulfur-based positive electrode active material, or may contain only the sulfur-based positive electrode active material. The sulfur-based positive electrode active material may contain sulfur, elemental sulfur (S 8 ), sulfur-based compounds having sulfur, etc., but are not limited thereto. For example, the sulfur-based positive electrode active material may include Li 2 S n (n is a real number greater than or equal to 1), organic sulfur complexes or carbon-sulfur complexes (C 2 S x ) n (x is a real number from 2.5 to 50, inclusive, and n is a real number of 2 or greater).

[0077] Meanwhile, in the present invention, the sulfur content in the sulfur-based positive electrode active material may be 60 wt% or more, 70 wt% or more, 80 wt% or more, or 90 wt% or more. In a specific embodiment, the sulfur-based positive electrode active material may be a carbon-sulfur composite, and the sulfur content in 100 wt% of the carbon-sulfur composite may be 60 wt% or more, 70 wt% or more, or 80 wt% or more.

[0078] Non-limiting examples of the conductive material include carbon-based materials such as carbon black, acetylene black, or ketjen black; and conductive polymers such as polyaniline, polythiophene, polyacetylene, and polypyrrole. The conductive material may account for about 1 wt% to 20 wt%, 1 wt% to 10 wt%, or 1 wt% to 7 wt% of the total weight of the positive electrode active material layer. If the conductive material is less than 1% of the total weight of the positive electrode active material layer, the effect or result of improving the conductivity (electrical conductivity) due to the conductive material may be negligible. In contrast, if the conductive material exceeds about 20 wt%, the amount of the positive electrode active material becomes relatively small, and the capacity of the battery 100 may be reduced or decreased. Meanwhile, the conductive material is different from that contained in the carbon material of the sulfur-carbon composite.

[0079] The binder is not limited to a specific material as long as it is a binder material for an electrochemical element, and can bind components in an electrode, such as an electrode active material, and can ensure a desired binding force between an electrode active material layer and a current collector. Non-limiting examples include acrylic binder polymers containing polyacrylic acid polymerized units, such as poly(methyl methacrylate) or poly(ethyl acrylate), fluorine-based binder polymers containing vinylidene fluoride polymerized units (such as polyvinylidene fluoride, polyvinylidene fluoride-co-polyhexafluoropropylene, polyvinylidene fluoride-co-trichloroethylene, polyvinylidene fluoride-co-tetrafluoroethylene, polyvinylidene fluoride-co-trifluoroethylene, polyvinylidene fluoride-co-trifluorochloroethylene, and polyvinylidene fluoride-co-ethylene), poly(vinyl acetate), polyvinyl alcohol, polyethylene oxide, (alkylated) polyethylene oxide, crosslinked polyethylene oxide, polyvinyl ether, polyvinylpyrrolidone, polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polystyrene, derivatives, blends, copolymers, and the like.

[0080] The binder may account for about 2 wt% to 10 wt% of the total weight of the positive electrode active material layer. If the binder content is less than 2 wt%, the effect or result of improving the adhesion between the positive electrode active material or the positive electrode active material and the positive electrode current collector may be insignificant. On the other hand, if the binder content exceeds 10 wt%, the amount of the positive electrode active material becomes relatively small, and the capacity of the battery 100 may be reduced or decreased.

[0081] In one embodiment of the present invention, the positive electrode 212 may be manufactured by applying a composition for forming a positive electrode active material layer, which is manufactured by adding a positive electrode material including a positive electrode active material, a conductive material, and a binder, to an organic solvent, and then drying the composition on the positive electrode current collector. If necessary, the electrode manufactured by the above-mentioned method may be pressurized to a predetermined thickness, and in that case, heat having a predetermined temperature may be applied if necessary. In one embodiment, the organic solvent may be a dispersion medium for the positive electrode material and may be a solvent that evaporates easily. The organic solvent may include, for example, one or more selected from methylpyrrolidone (NMP), acetonitrile, methanol, ethanol, tetrahydrofuran, water, and isopropyl alcohol. The positive electrode material may be prepared in a dry mixed state without adding an organic solvent, or in a wet state with a small amount of solvent added. The positive electrode may be manufactured by applying the positive electrode material to the surface of the positive electrode current collector and then pressing it.

[0082] According to an embodiment of the present invention, the negative electrode 216 includes a negative electrode active material layer including a negative electrode active material. If necessary, the negative electrode may include a negative electrode current collector, in which case a negative electrode active material layer (not shown) may be disposed on at least one surface of the negative electrode current collector or on the positive electrode surface.

[0083] In one embodiment, the negative electrode current collector may be selected from the group consisting of copper, aluminum, stainless steel, titanium, silver, palladium, nickel, alloys thereof, and combinations thereof. The stainless steel may be surface-treated with carbon, nickel, titanium, silver, or the like, and the alloy may be an aluminum-cadmium alloy. In addition, calcined carbon, surface-treated non-conductive polymers, conductive polymers, or the like may be used as precursors.

[0084] The negative electrode active material may be lithium metal, a carbon material including crystalline carbon, amorphous carbon, or a combination of crystalline carbon and amorphous carbon, tin, tin oxide (SnO 2 etc.), lithium titanium oxide (LTO), titanium nitrate, silicon (Si), silicon oxide, alloys of lithium with metals Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, or Cd, etc.

[0085] In an embodiment of the present invention, when lithium metal is used as the negative electrode active material, the lithium metal may form a thin film and be bound to the current collector.

[0086] Additionally or alternatively, the negative electrode active material layer may include a conductive material and a binder together with the negative electrode active material. The type and content of the conductive material and / or binder are substantially similar to the conductive material and binder described above in connection with the positive electrode 212 of the present invention.

[0087] According to an embodiment of the present invention, the separator 214 of the electrode assembly 210 is a battery component disposed between the positive electrode 212 and the negative electrode 216 to electrically insulate the positive electrode from the negative electrode and provide a path for ion migration. The separator may be any suitable separator for a lithium secondary battery. According to an embodiment of the present invention, it is preferable to use a separator having low resistance and excellent electrolyte absorption properties. The separator may include a porous polymer film, a nonwoven fabric made of a polymer material, a glass fiber having a eutectic point, and the like. Non-limiting examples of the polymer include porous polymers made of polyolefin-based polymers such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, and ethylene / methacrylate copolymer. These polymer films may be used in a single layer or in a multilayer form by laminating multiple layers.

[0088] 3 is a schematic diagram of a battery manufacturing system 300 for manufacturing lithium secondary batteries according to one embodiment of the present invention. The system 300 may include a controller 302, an electrolyte dispensing unit 304, and a jig 306.

[0089] In one embodiment of the present invention, the jig may be configured with two parallel plates, and the gap between the plates may be narrowed to uniformly apply pressure to a component (e.g., a battery) placed between the plates. Also, when pressure is applied by the jig and released, the plates can be maintained parallel.

[0090] In one embodiment of the present invention, a battery may be disposed between two flat plates of the jig, and the stacking direction of the electrode assembly may be perpendicular to the direction in which the flat plates are disposed. That is, the electrode plates (positive and / or negative electrodes) included in the electrode assembly and the flat plates may be disposed in parallel.

[0091] In one embodiment of the present invention, the system may further include a thickness measurement unit having a thickness measurement sensor for measuring the thickness of the battery. For example, the thickness measurement unit may be included in the jig or may be connected to the jig. When a battery is inserted between two flat plates of the jig, for example, between an upper plate which is a first flat plate and a lower plate which is a second flat plate, the thickness measurement sensor measures the distance between the upper plate and the lower plate of the jig to recognize the thickness of the battery. The system may further include a calculation device (not shown), which calculates an SF value based on the thickness value of the battery sent from the thickness measurement sensor and sends it to the control device. Meanwhile, the time when the thickness measurement sensor measures the thickness may be automatically controlled by the control device or manually by an operator.

[0092] In one embodiment of the present invention, the thickness T1 of the battery before electrolyte injection may be the distance between the upper plate and the lower plate of the jig when the distance between the upper plate and the lower plate of the jig is reduced and the first plate (upper plate) of the jig comes into contact with the battery after the battery is placed on the second plate (lower plate) of the jig. That is, the thickness T1 is the thickness in a state where no pressure is applied to the battery. Also, the thickness T1 may be measured using a contact or non-contact thickness measuring device other than the jig and then input to the arithmetic device. Meanwhile, the thickness T2 of the battery after electrolyte injection may be continuously measured at a predetermined time interval by the sensor while injecting the electrolyte. In this case, the arithmetic device may continuously measure the SF value, which may be sent to the control device, and the pressure may be adjusted so that the measured SF value is less than 10, 7 or less, 5 or less, or 3 or less.

[0093] Meanwhile, after the electrolyte injection is completed, the value of the thickness T2 of the battery may be measured. In this case, the measurement may be performed while the pressure applied to the battery is maintained. Alternatively, the T2 may be measured while the pressure applied to the battery is released. The thickness T2 of the battery after the pressure is released may be measured by the same method as the thickness measurement method of T1 described above. Alternatively, the thickness of the battery may be measured by various contact or non-contact thickness measurement devices known in the technical field of thickness measurement, in addition to the method using a jig. Meanwhile, the measurement of the thicknesses T1 and T2 for confirming SF' may be performed while the pressure applied to the battery is maintained, or may be measured while the pressure applied to the battery is released.

[0094] In one embodiment, the system 300 may also include a machine or device (not shown) for manufacturing the electrode assembly 210, such as a device for mounting the electrode assembly in the housing 102.

[0095] The controller 302 may be configured to facilitate a battery manufacturing process described herein, such as the process illustrated in FIG. 5. The controller 302 may include a computer system or one or more processors of a computer system. The processes or process steps performed by the computer system and one or more processors may refer to operations. The one or more processors may be configured to perform such processes by accessing instructions (e.g., software or computer readable code) that, when executed by the one or more processors, cause the one or more processors to perform a process. The instructions (commands) may be stored in a memory of a computer system. The processor may be a central processing unit (CPU), a graphics processing unit (GPU), or other type of processing device.

[0096] In one embodiment, the controller 302 can automatically control the electrolyte dispensing unit 304 to inject a predetermined amount of electrolyte into the battery 200. Alternatively, an operator can operate the controller 302 and / or the electrolyte dispensing unit 304 to manually inject the electrolyte.

[0097] In one embodiment, the controller 302 may be configured to apply pressure (or force) to one or more sides of the jig 306. The pressure may be applied from a first direction 308 and / or a second direction 310. In one embodiment, the jig 306 may include one or more pressure devices (or mechanisms) configured to apply pressure from at least the first direction 308 and / or the second direction 310. The controller 302 may be configured to control the amount of pressure applied by or from the jig 306 to the battery 200. In one embodiment, the jig 306 may be configured to apply the same or constant pressure to each of a single surface or all of the surfaces. Additionally or alternatively, the jig 306 may be configured to apply different amounts of pressure to different surfaces of the battery 200, or to different areas of a single surface, or to each of multiple surfaces of the battery 200.

[0098] In one embodiment, the jig 306 may be configured to apply pressure to the battery 200 based on a given battery's structure (e.g., thickness of the battery before electrolyte injection) and structural strength (e.g., tensile or elastic strength of the battery). For example, based on the size, material, and shape of the jig 306, various amounts of pressure may be applied to the battery 200 without additional external force or pressure being applied to the jig 306. For example, the jig 306 may be a container, a housing, etc., alternatively or additionally, applying one or more configurable pressures to or from the jig 306, and a pressure device (or mechanism) may be coupled to or incorporated into the jig 306 to facilitate application of one or more pressures. For example, the pressure device may include a motor, a spring, etc. In one embodiment, the controller 302 may be configured to automatically or manually adjust the amount of pressure applied or pressure applied from the jig to the battery through one or more pressure devices or mechanisms, where the amount of pressure may be determined by operation of the system 300.

[0099] As described above, in the case of the Li-S battery according to the present invention, non-uniform impregnation of the electrolyte may occur due to the low porosity of the high density positive electrode. For example, when the electrolyte is injected into the housing of the battery 200 without applying pressure or force to the battery 200, strong capillary action may occur at the position where the positive electrode contacts the electrolyte. Therefore, excessive swelling may occur at or near the initial contact point between the positive electrode and the electrolyte. Such excessive swelling may prevent the electrolyte from being distributed or distributed to other regions of the positive electrode of the battery 200. In this case, the positive electrode may include pores where the electrolyte is not uniformly distributed or is not impregnated with the electrolyte, which may result in a decrease in electrochemical performance such as life characteristics. FIG. 8 is a schematic diagram of a shape in which the thickness of a battery is manufactured non-uniformly due to volume expansion at the position of the electrolyte injection port when the electrolyte is injected.

[0100] Referring to FIG. 3, the battery 200 may be a Li-S battery containing sulfur as a positive electrode active material. The positive electrode active material layer 212 may have a density of 0.5 g / cc to 1.3 g / cc or 0.7 to 1.3 g / cc. The density of the positive electrode active material layer may be an apparent density, and the apparent density may be calculated by {weight (g) of the positive electrode active material layer / volume (cc) of the positive electrode active material layer}. In one embodiment of the present invention, the positive electrode 212 may have a porosity of 75 vol% or less, 70 vol% or less, or 65 vol% or less. Meanwhile, the porosity of the positive electrode may be 35 vol% or more. If the porosity of the positive electrode is less than 35 vol%, problems may occur in ion transport. Meanwhile, if the porosity is more than 75 vol%, the energy density and the mechanical strength of the electrode are reduced. Also, the amount of electrolyte injected may increase. In the unlikely event that the porosity exceeds 75 vol%, when an electrolyte having an appropriate E / S range is injected as described below, the electrolyte may not be impregnated into the entire electrode assembly. Meanwhile, the porosity (vol%) may be calculated by [{1-(apparent density / true density)}×100]. The true density may be measured from the components of the materials contained in the positive electrode active material layer and the density of each component. Alternatively, the porosity may be measured by the mercury intrusion method of ASTM D 4284-92 using an apparatus such as an autoprore IV 9500 by Micrometrics.

[0101] In an embodiment of the present invention, the weight ratio of electrolyte to sulfur (E / S) in the battery 200 may be 2.7 or less. The weight of sulfur refers to the weight of sulfur contained in the positive electrode active material of the positive electrode 212, and the weight of electrolyte refers to the weight of electrolyte injected into the battery. For example, the ratio E / S may be greater than 0, greater than or equal to 1.0, or greater than or equal to 1.5. Meanwhile, the ratio E / S may be less than or equal to 2.7, less than or equal to 2.5, or less than or equal to 2.0. The ratio E / S being 0 (E / S=0) may indicate that there is no electrolyte, for example, a state before electrolyte is injected into the battery 200. Meanwhile, the ratio E / S exceeding 2.7 (e.g., E / S>2.7) may indicate that the porosity of the positive electrode 212 of the battery 200 is too high, and thus an excessive amount of electrolyte is present in the battery 200. This means that the density of the positive electrode is not within an appropriate range.

[0102] As shown in FIG. 3, the system 300 according to the present invention can manufacture a cell 200 with minimal or no volume expansion of the battery due to a pressurizing process. In one embodiment, the battery 200 can be inserted, placed, or arranged in a jig 306 before an electrolyte is injected into the battery 200. In one embodiment, the battery 100 can be a Li-S battery. The electrode assembly (e.g., electrode assembly 210) of the Li-S battery can include a high density positive electrode 212 with low porosity. For example, the electrode assembly 210 can be a lithium ion battery including a high density positive electrode having a density of 0.5 g / cc to 4.5 g / cc or 0.7 g / cc to 4.5 g / cc. In this specification, the density of the electrode means the density of the electrode active material layer. That is, in this specification, the density of the positive electrode means the density of the positive electrode active material layer.

[0103] In one embodiment of the present invention, the density of the positive electrode of the present invention may be 0.5 g / cc or more, 0.7 g / cc or more, 0.8 g / cc or more, or 0.9 g / cc or more. The density of the positive electrode may be 4.5 g / cc or less, or 4.0 g / cc or less. If the density of the positive electrode is excessively high beyond the above range, the battery life and / or battery performance may be reduced or deteriorated. In particular, the positive electrode of the present invention contains a sulfur-based positive electrode active material as a positive electrode active material, and preferably has a density of 0.7 g / cc or more. The upper limit of the density of the positive electrode may be appropriately adjusted within the above range.

[0104] According to the present invention, when manufacturing a battery, specifically when injecting an electrolyte, a pressurizing process may be performed so that the electrolyte is uniformly impregnated into the pores of the positive electrode. The pressurizing process may be performed based on one or more of a number of factors including the porosity and density of the positive electrode, the ratio E / S, and the shape and size of the battery.

[0105] In one embodiment of the present invention, the amount of pressure applied during the pressurizing process may be controlled based on the thickness of the cell, specifically T1 and T2. While the electrolyte is being injected, T2 may be continuously measured by a thickness measuring device connected to the jig. Based on the measured T2, a relatively strong pressure may be applied to a battery with a large SF (large degree of expansion) in order to reduce the expansion, and a relatively weak pressure may be applied to a battery with a small SF (small degree of expansion). Since the injection is performed within a limited space where the position is fixed by the thickness of the cell, the expansion of the electrodes that occurs when the electrolyte is impregnated can be suppressed.

[0106] In one embodiment of the present invention, the pressure during pressurization may be 100 atm or less. For example, the pressure may be 0.1 atm to 100 atm, 1 atm to 100 atm, 3 atm to 100 atm, or 5 atm to 100 atm. As a specific example, the pressure may be 100 atm or less, 70 atm or less, 50 atm or less, 30 atm or less, or 10 atm or less. If the pressure is less than 0.1 atm, the thickness of the battery may not be kept constant. That is, if the pressure applied to the battery housing is insufficient, excessive expansion may occur at the position where the electrolyte first contacts the electrode assembly (or the positive electrode), causing the thickness of the battery to increase. Alternatively, if the pressure during pressurization exceeds 100 atm, excessive pressure may be applied to the housing, causing deformation, contraction, or damage to components of the electrode assembly, such as the electrodes and separators. Meanwhile, in one embodiment of the present invention, the pressure is preferably maintained such that T2, which is continuously measured during electrolyte injection, is equal to or higher than T1, that is, the SF value is maintained in a range of 0 or more.

[0107] As shown in FIG. 3, the amount of pressure applied to the battery 200 from or by the jig 306 can be adjusted based on the desired expansion coefficient SF of the battery 200.

[0108] In one embodiment of the present invention, the expansion coefficient SF of the battery 100 and / or the battery 200 may be defined as the following Equation 1:

[0109] [Formula 1] SF=(T2-T1) / (T1)×100.

[0110] In one embodiment of the present invention, in Equation 1, SF is the expansion coefficient, T1 refers to the thickness of the battery 200 before the electrolyte is injected into the housing 102, and T2 refers to the thickness of the battery 200 after the electrolyte is injected into the housing 102. Additionally or alternatively, T1 may be the thickness of the battery at any first location on the battery surface, and T2 may be the thickness of the battery at any second location different from T1.

[0111] Referring to FIG. 4a, FIG. 4a exemplarily illustrates thickness measurement zones of the battery 200. In one embodiment, the thickness T1 of the battery 200 may be measured before the electrolyte is injected into the housing. In one embodiment, the battery 200 may include zone A, zone B, and zone C, and the thickness of the battery 200 may be measured in zone A, zone B, and / or zone C individually or in combination. Although three zones are shown in this embodiment, the number of measurement zones may be changed. In a specific embodiment of the present invention, the thickness may be measured at one or more specific points in each zone.

[0112] FIG. 4B exemplarily illustrates thickness measurement zones of the battery 200. In one embodiment, the thickness T2 of the battery 200 may be measured after the electrolyte is injected into the housing. In one embodiment, the battery 200 may include zone A, zone B, and zone C. The thickness of the battery 200 may be measured in zone A, zone B, and / or zone C individually or in combination. Although three zones are shown in this embodiment, the number of measurement zones may be changed. In a specific embodiment of the present invention, the thickness may be measured at one or more specific points in each zone.

[0113] As shown in FIG. 3 to FIG. 4b, the battery manufacturing system 300 according to the present invention can manufacture the battery 200 having an expansion coefficient in the range of 0≦SF<10. This SF range indicates that the battery 200 will have minimal or no swelling after the electrolyte is injected into the battery. As described above, when the electrolyte is injected into the housing of the battery 200, the electrolyte fills the vacant space 204 in the housing. Thus, any change in the thickness of the battery 200 after the electrolyte is injected indicates that the electrolyte is not uniformly impregnated into the housing. Thus, an expansion coefficient greater than 0 can indicate that the electrolyte does not completely fill the pores of the electrode assembly and the vacant space inside the battery 200. If the SF value is 10 or more, it can indicate that there is excess electrolyte that has not been impregnated into the internal pores of the electrodes. On the other hand, the thickness of the battery is not substantially reduced, so that SF<0 is unlikely to occur after the electrolyte is injected. When the electrolyte is completely and uniformly impregnated into the pores of the electrodes and excess electrolyte (an amount of electrolyte equal to or greater than the pore volume of the electrode assembly) is fully filled into the dead space of the battery 200, the expansion coefficient is substantially SF=0. On the other hand, when the expansion coefficient does not exceed 10, there is substantially no significant change in thickness, so in the present invention, when SF is a value between 0 and less than 10, it is considered that the electrolyte is uniformly filled in the electrode assembly. According to a specific embodiment of the present invention, the expansion coefficient of the battery 200 may be 0≦SF<10, 0≦SF≦7, 0≦SF≦5, 0≦SF≦3, 0≦SF≦2, or 0≦SF≦1, preferably SF is 5 or less, and most preferably SF is 0.

[0114] Meanwhile, after injecting an electrolyte into the pouch battery to completely fill the pores of the electrode assembly with the electrolyte, the remaining electrolyte is filled into the empty space 204 in the pouch. The empty space is a space that is usually present inside the pouch, and is a space into which the remaining electrolyte may flow after the electrolyte is filled into the pores of the electrode. Therefore, when an amount of electrolyte corresponding to the volume of the pores in the electrode assembly is injected in consideration of the volume of the pores in the electrode assembly, in some cases, the electrolyte does not flow completely into the electrode assembly and remains outside the electrode assembly, but is filled into the empty space 204, so that SF may have a value less than 10, 7 or less, 5 or less, or less, and preferably has a value close to 0.

[0115] Therefore, by constructing the positive electrode with low porosity and high density, particularly in lithium-sulfur batteries, the positive electrode can be constructed with high density and low porosity to enable the battery to be powered or operated with improved performance even when using less electrolyte than conventional Li-S batteries.

[0116] The lithium secondary battery according to the present invention includes a high density electrode and has a low E / S ratio, and is uniformly impregnated with an electrolyte, thereby realizing a high capacity lithium secondary battery.

[0117] In this specification, the lithium secondary battery means that the ratio E / S is in the above-mentioned range, and the weight of the electrolyte relative to the weight of sulfur contained as the positive electrode active material is equal to or less than a certain value.

[0118] In the present invention, the lithium secondary battery has a high capacity because the density of the positive electrode is high and the electrolyte is uniformly introduced into the electrode assembly to have a uniform thickness. s ~1300mAh / g s Specifically, the capacity of the lithium secondary battery may be 950mAh / g. s More than 1000mAh / g s or more than 1050mAh / g sThe capacity of the secondary battery may be 1300 mAh / g or more. s Below, 1250mAh / g s Less than or equal to 1200mAh / g s The battery capacity is based on the capacity per unit weight (g) of the positive electrode active material, i.e., sulfur.

[0119] On the other hand, in the present invention, the electrolytic solution may contain an organic solvent and a lithium salt, and may be a liquid electrolytic solution.

[0120] The organic solvent serves as a medium through which ions involved in the electrochemical reaction of the battery can move. As the organic solvent, any organic solvent that is commonly used in electrolytes for lithium secondary batteries can be used without limitation, and for example, ethers, esters, amides, chain carbonates, cyclic carbonates, etc. may be used alone or in combination of two or more. Among them, ether-based compounds are representative.

[0121] The ether-based compound may include acyclic ethers and cyclic ethers.

[0122] For example, the acyclic ether may be one or more selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether.

[0123] For example, the cyclic ether may be dioxolane, 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, isosorbide dimethyl ether (isosorbdimethyl ether), furan, 2-methylfuran, 3-methylfuran, 2-ethylfuran, 2-butylfuran, 2,3-dimethylfuran, 2,4-dimethylfuran, 2,5-dimethylfuran, pyran, 2-methylpyran, 3-methylpyran, 4-methylpyran, benzofuran, 2-(2-nitrovinyl)furan, thiophene, 2-methylthiophene, 2-ethylthiophene, 2-propylthiophene, 2-butylthiophene, 2,3-dimethylthiophene, 2,4-dimethylthiophene, and 2,5-dimethylthiophene, but are not limited thereto.

[0124] Examples of the ester of the organic solvent include, but are not limited to, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone, and mixtures of two or more of these.

[0125] Specific examples of the chain carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more of these.

[0126] Specific examples of the cyclic carbonate compound include ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof, or mixtures of two or more of these. Examples of such halides include, but are not limited to, fluoroethylene carbonate (FEC).

[0127] The lithium salt is a compound capable of supplying lithium ions to the electrolyte. Examples of such lithium salts include LiPF 6 , LiClO 4 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlO 4 , LiAlCl 4 , LiCF 3 CO 2 , LiCF 3 SO 3 , LiC 4 F 9 SO 3 , LiN(C 2 F 5 SO 3 ) 2 , LiCH 3 SO 3 , LiN(C 2 F 5 SO 2 ) 2 , LiN(CF 3 SO 2 ) 2 , LiC4 BO 8 , LiCl, LiBr, LiB 10 Cl 10 , LiI, or LiB(C 2 O 4 ) 2 In the present invention, in order to increase the possibility of utilizing sulfur and realize a high-capacity and high-voltage battery, it is preferable that the lithium salt contains Li-TFSI. More preferably, the lithium salt contains LiN(CF) at a content of 80 wt% or more, 90 wt% or more, or 100 wt% based on 100 wt% of the total lithium salt. 3 SO 2 ) 2 (Li-TFSI).

[0128] The concentration of the lithium salt is in the range of 0.1 to 2.0 M, preferably 0.5 to 1 M, more preferably 0.5 to 0.75 M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore can have excellent performance and lithium ion mobility. When the concentration of the lithium salt is below the above range, it may be difficult to ensure ion conductivity suitable for driving the battery, and when it exceeds the above range, the viscosity of the electrolyte increases, which may reduce the mobility of lithium ions, or the decomposition reaction of the lithium salt itself may increase, which may reduce the performance of the battery.

[0129] In addition to the components of the electrolyte, the electrolyte may further contain additives for the purpose of improving the life characteristics of the battery, suppressing the decrease in the battery capacity, improving the discharge capacity of the battery, etc. For example, the additives may be nitric acid compounds, nitrous acid compounds, haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, which may be used alone or in combination. The additives may be contained in an amount of 0.1 to 10 wt%, preferably 0.1 to 5 wt%, based on the total weight of the electrolyte.

[0130] In a specific embodiment of the present invention, the electrolyte may contain a nitric acid compound and / or a nitrite-based compound as an additive. The nitric acid compound / nitrite-based compound has the effect of forming a stable coating on the lithium metal electrode, which is the negative electrode, and improving the charge / discharge efficiency. Examples of such nitric acid or nitrite-based compounds include lithium nitrate (LiNO 3 ), potassium nitrate (KNO 3 ), Cesium nitrate (CsNO 3 ), barium nitrate (Ba(NO 3 ) 2 ), ammonium nitrate (NH 4 NO 3 ), lithium nitrite (LiNO 2 ), potassium nitrite (KNO 2 ), Cesium nitrite (CsNO 2 ), ammonium nitrite (NH 4 NO 2), inorganic nitric acid or nitrite compounds such as methyl nitrate, dialkylimidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrite, propyl nitrite, butyl nitrite, pentyl nitrite, octyl nitrite, organic nitric acid or nitrite compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene, and combinations thereof. In a preferred embodiment of the present invention, the additive may include lithium nitrate.

[0131] 5 is a process flow diagram illustrating an exemplary method 500 for manufacturing a lithium secondary battery according to the present invention. The battery may be manufactured by the battery manufacturing system 300 described above.

[0132] First, an electrode assembly is formed by stacking a first electrode, a separator, and a second electrode (step 502). In one embodiment, the first electrode may be a positive electrode, and the second electrode may be a negative electrode. Then, the electrode assembly is inserted into a housing (step 504). In one embodiment, the housing may be a pouch. The housing into which the electrode assembly is inserted is placed in a jig. In one embodiment, the thickness T1 of the battery may be measured before or after it is placed in the jig. Then, pressure may be applied to the surface of the inserted battery (step 506). The pressure may be controlled to exhibit a desired expansion coefficient SF. In one embodiment, the amount of pressure may be controlled to a degree that satisfies the above conditions at 100 atm or less. In one embodiment, the expansion coefficient SF of the battery may be 0 to less than 10. Then, a predetermined amount of electrolyte is injected into the housing (step 508). Meanwhile, as described above, the thickness of the battery may be measured while injecting the electrolyte, and the amount of pressure applied to the battery may be appropriately controlled based on the measured thickness. The amount of pressure may be controlled based on the SF value. After the electrolyte injection is completed, the battery is then sealed (step 510). Meanwhile, the expansion coefficient of the battery may be measured before the sealing. In another embodiment, the expansion coefficient may be measured after the pouch is sealed. In yet another embodiment, the thickness of T2 may be measured before or after the pressure applied to the battery is released. The expansion coefficient SF is calculated based on the above formula 1. In one embodiment of the present invention, the expansion coefficient T2 may be measured before or after the pressure is released, and may have a value of 0 or more and less than 10, preferably 7 or less, more preferably 5 or less, and even more preferably 3 or less.

[0133] In one embodiment of the present invention, after the pressure on the battery is released, the thicknesses T1 and T2 may be measured at any two points, and the SF value may be calculated from the thicknesses T1 and T2.

[0134] Illustrative examples are presented to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications can be made without departing from the scope and spirit of the present invention. Various changes and modifications are intended to be included in the scope of the appended claims.

[0135] Example 1 (1) Manufacturing of electrode assemblies A sulfur-carbon composite was prepared as a positive electrode active material. Sulfur (S) and carbon (e.g., CNT) were uniformly mixed in a solid state (S:CNT = 75:25, weight ratio) and then heat-treated at 155 °C for 35 minutes to produce a sulfur-carbon composite. The positive electrode active material (sulfur-carbon composite) and CNT (specific surface area 300 m 2 A positive electrode active material layer forming composition was prepared by mixing 100% ethylenediaminetetraacetate (ethylenediaminetetraacetate, 100% ethylenediaminetetraacetate, 100% ethylenediaminetetraacetate) and SBR (styrene butadiene rubber) in a ratio of 90:5:5 (weight ratio) using a mixer. This composition was mixed with ethanol as an organic solvent to prepare a positive electrode active material layer forming slurry, which was then coated on an Al current collector, dried, and pressed to prepare a positive electrode.

[0136] In addition, a lithium metal thin film was prepared as a negative electrode. The prepared positive electrode and negative electrode were positioned facing each other, and a polyethylene separator was interposed between the positive electrode and the negative electrode to prepare an electrode assembly.

[0137] (2) Pressurization A pressure jig with an upper plate and a lower plate arranged in parallel was prepared, and the pouch containing the electrode assembly was placed in the jig, and then pressurized to about 5 atmospheres (atm) to maintain the thickness of the pouch cell constant.

[0138] (3) Electrolyte injection The electrolyte was prepared by adding 1 mol of LiTFSI to a mixed organic solvent of tetraethylene glycol dimethyl ether (TEGDME) / dioxolane (DOL) / dimethoxyethane (DME) (1:1:1 volume ratio). 3was added at a weight ratio of 1 / 10 of LiTFSI. After the electrolyte was injected, the pressure was reduced for about 3 seconds to maintain a vacuum state. After that, the electrolyte was completely injected, and the jig was removed from the pouch cell.

[0139] Comparative Example 1 A pouch cell type Li-S secondary battery was manufactured in the same manner as in Example 1, except that the pressurizing steps before and after the electrolyte injection were not performed.

[0140] Test Example 1 The performance of the Li-S secondary batteries manufactured in Example 1 and Comparative Example 1 was tested.

[0141] (1) Initial discharge capacity and battery life A charge-discharge test was conducted on the Li-S secondary battery manufactured in a pouch cell type by repeatedly charging and discharging at room temperature. After the first discharge at 0.1C, the same charge-discharge cycle was repeated two more times, and then three times at 0.2C, followed by continuous charge-discharge at 0.3C / 0.5C. A capacity-voltage graph at the first discharge was obtained to evaluate the initial discharge capacity, and a capacity change graph due to repeated cycles was obtained to evaluate the high-speed performance.

[0142] (2) 0.1C nominal voltage (V) 0.1C nominal voltage was measured using a PNESOLUTION charger / discharger.

[0143] (3) Electrolyte / sulfur ratio The weight of each sulfur was measured, and then the weight ratio was calculated.

[0144] (4) Energy density (Wh / kg) The energy density was calculated by dividing the pouch cell capacity (Wh) by the pouch cell weight (kg).

[0145] (5) Measurement of the expansion coefficient SF The expansion coefficient was calculated based on the following formula 1.

[0146] [Formula 1] SF = (thickness of pouch cell after electrolyte injection - thickness of pouch cell before electrolyte injection) / (thickness of pouch cell before electrolyte injection) x 100

[0147] [Table 1]

[0148] 6 is a graph 600 comparing the initial discharge capacity of Example 1 manufactured according to one embodiment of the present invention with that of Comparative Example 1. As can be seen from Table 1 and graph 600, it was confirmed that the battery of Example 1 has superior initial discharge capacity characteristics compared to the battery of Comparative Example 1.

[0149] 7 is a graph 700 comparing the discharge cycle characteristics of Example 1 manufactured according to one embodiment of the present invention with Comparative Example 1. As can be seen from Table 1 and graph 700, it was confirmed that the battery of Example 1 has superior life characteristics compared to the battery of Comparative Example 1.

[0150] Also, Example 1 exhibits superior 0.1C discharge nominal voltage and energy density compared to Comparative Example 1. Although the electrolyte / sulfur ratios of Example 1 and Comparative Example 1 are the same, Example 1 is superior to Comparative Example 1 in all other physical properties, because the electrolyte was uniformly injected through the pressurization process. [Explanation of symbols]

[0151] 100 batteries 102 Housing 104 First electrode tab 106 Second electrode tab 104a Insulating protective tape 106a Insulating protective tape 200 batteries 202 Opening (electrolyte inlet) 210 Electrode assembly 204 Dead Space 210 Electrode assembly 212 Positive electrode 214 Separator 216 negative electrode 218 Final Floor 300 Systems 304 Electrolyte dispensing unit 302 Controller 306 Jig 308 Second direction 308 1st direction

Claims

1. A lithium-sulfur battery having a sulfur-based compound as a positive electrode active material, an electrode assembly including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode; a pouch for accommodating the electrode assembly; An electrolyte; Including, The lithium-sulfur battery has a thermal expansion coefficient (SF) of 0 to less than 10 according to the following formula 1: The lithium-sulfur battery has an expansion coefficient (SF') of 0 to 7 according to the following formula 2: The positive electrode has a density of a positive electrode active material layer of 0.5 g / cc to 4.5 g / cc. [Formula 1] SF=(T2-T1) / (T1)×100 where T1 is the first thickness of the lithium-sulfur battery and T2 is the second thickness of the lithium-sulfur battery. the first thickness being a thickness of the lithium-sulfur battery before injecting an electrolyte into the pouch, and the second thickness being a thickness of the lithium-sulfur battery after injecting an electrolyte into the pouch; [Formula 2] SF'=(T4-T3) / (T3)×100 where T3 is the third thickness of the lithium-sulfur battery and T4 is the fourth thickness of the lithium-sulfur battery. The third thickness and the fourth thickness are both measured after injecting an electrolyte, and the third thickness and the fourth thickness are each measured at an arbitrary location of the battery, and the measurement locations of the third thickness and the fourth thickness are different from each other.

2. 2. The lithium-sulfur battery according to claim 1, wherein the positive electrode comprises a sulfur-carbon composite having a carbon material and sulfur as a positive electrode active material.

3. 3. The lithium-sulfur battery according to claim 2, wherein the weight of sulfur is 70% or more based on the total weight of the sulfur-carbon composite.

4. 2. The lithium-sulfur battery of claim 1, wherein the negative electrode comprises lithium as a negative electrode active material.

5. 3. The lithium-sulfur battery of claim 2, wherein the ratio of the weight of the electrolyte to the weight of the sulfur, E / S, is 2.7 or less.

6. 2. The lithium-sulfur battery according to claim 1, wherein the positive electrode active material layer of the positive electrode has a porosity of 35 vol % to 75 vol %.

7. The capacity of the lithium-sulfur battery is 950 mAh / g s ~1300mAh / g s 2. The lithium-sulfur battery of claim 1,

8. 13. An electric vehicle comprising the lithium-sulfur battery of claim 1 as a power source.

9. 1. A method for manufacturing a lithium-sulfur battery, comprising: stacking the positive electrode, the separator, and the negative electrode to form an electrode assembly; housing the electrode assembly in a pouch; applying a predetermined pressure to a pouch containing the electrode assembly; injecting a quantity of electrolyte into the pouch while maintaining the predetermined pressure; sealing the pouch; Including, The lithium-sulfur battery has a thermal expansion coefficient (SF) of 0 to less than 10 according to the following formula 1: The positive electrode has a positive electrode active material layer having a density of 0.5 g / cc to 4.5 g / cc. [Formula 1] SF=(T2-T1) / (T1)×100 where T1 is the first thickness of the lithium-sulfur battery and T2 is the second thickness of the lithium-sulfur battery. The first thickness is the thickness of the lithium-sulfur battery before the pouch is filled with electrolyte, and the second thickness is the thickness of the lithium-sulfur battery after the pouch is filled with electrolyte.

10. The method for manufacturing a lithium-sulfur battery of claim 9, further comprising the step of measuring a expansion factor (SF) before sealing the pouch.

11. 11. The method of claim 10, wherein the measuring the expansion coefficient comprises: measuring a first thickness of the lithium-sulfur battery before injecting an electrolyte into the pouch; and measuring a second thickness of the lithium-sulfur battery after injecting an electrolyte into the pouch.

12. The method for manufacturing a lithium-sulfur battery of claim 9, further comprising the step of measuring an expansion coefficient after sealing the pouch.

13. the step of measuring the expansion coefficient includes the steps of measuring a third thickness of the battery in a first area of ​​the lithium-sulfur battery and measuring a fourth thickness of the battery in a second area of ​​the lithium-sulfur battery; The method for manufacturing the lithium-sulfur battery according to claim 12, wherein the lithium-sulfur battery has an expansion coefficient (SF') of 0 to 7 according to the following formula 2: [Formula 2] SF'=(T4-T3) / (T3)×100 where T3 is the third thickness of the lithium-sulfur battery and T4 is the fourth thickness of the lithium-sulfur battery. The third thickness and the fourth thickness are both measured after injecting an electrolyte, and the third thickness and the fourth thickness are each measured at an arbitrary location of the battery, and the measurement locations of the third thickness and the fourth thickness are different from each other.

14. 10. The method for producing a lithium-sulfur battery of claim 9, wherein the amount of pressure is less than or equal to 100 atm.

15. 1. A system for manufacturing a lithium-sulfur battery, comprising: A control device; a jig connected to the controller, the jig having a first plate and a second plate, the jig applying pressure between the first plate and the second plate, the amount of pressure being based on an expansion coefficient of the lithium-sulfur battery; an electrolyte injection device connected to the control device and configured to inject an electrolyte into a pouch of the lithium-sulfur battery; Including, The expansion coefficient (SF) is expressed by the following formula 1: the lithium-sulfur battery includes an electrode assembly having a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode; The positive electrode has a positive electrode active material layer having a density of 0.5 g / cc to 4.5 g / cc. [Formula 1] SF=(T2-T1) / (T1)×100 where T1 is the first thickness of the lithium-sulfur battery and T2 is the second thickness of the lithium-sulfur battery. The first thickness is the thickness of the lithium-sulfur battery before the pouch is filled with electrolyte, and the second thickness is the thickness of the lithium-sulfur battery after the pouch is filled with electrolyte.

16. 16. The lithium-sulfur battery manufacturing system of claim 15, further comprising a controller that adjusts the amount of pressure applied to the lithium-sulfur battery based on the expansion coefficient.

Citation Information

Patent Citations

  • Method for manufacturing lamination type secondary battery

    JP2009146602A

  • Lithium sulfur battery

    JP2020013732A

  • How to improve the lifespan of lithium secondary batteries

    JP2020533746A

  • Positive electrode for lithium secondary battery containing goethite and lithium secondary battery including the same

    JP2021517727A

  • Electrolyte for lithium-sulfur battery and lithium-sulfur battery comprising thereof

    KR1020210113055A